1990
DOI: 10.1093/carcin/11.5.745
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the effects of dietary beef tallow and corn oil on pancreatic carcinogenesis in the hamster model

Abstract: We previously reported an enhancement of pancreatic carcinogenesis induced by N-nitrosobis(2-oxopropyl)amine (BOP) in hamsters fed diets containing high levels of corn oil. The research presented here compared diets high in corn oil with those high in beef tallow in the enhancement of pancreatic carcinogenesis. Pancreatic cancer was induced with 20 mg BOP/kg body wt, s.c. administered at 8 weeks of age. One week later, hamsters were assigned to one of five diet treatments: (i) 4.3% corn oil (control); (ii) 20.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1990
1990
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Decreased b-cell mass and function can lead to type 2 diabetes (55), which is an established risk factor for pancreatic cancer. High levels of dietary fat can also cause pancreatic hypertrophy or hyperplasia, which may increase the vulnerability of the pancreas to other carcinogenic insults (56,57). Bile acids are also hypothesized to promote pancreatic cancer, as bile acids stimulate the tumor promoter cyclooxygenase-2 in cell lines (4,(58)(59)(60)(61).…”
Section: Discussionmentioning
confidence: 99%
“…Decreased b-cell mass and function can lead to type 2 diabetes (55), which is an established risk factor for pancreatic cancer. High levels of dietary fat can also cause pancreatic hypertrophy or hyperplasia, which may increase the vulnerability of the pancreas to other carcinogenic insults (56,57). Bile acids are also hypothesized to promote pancreatic cancer, as bile acids stimulate the tumor promoter cyclooxygenase-2 in cell lines (4,(58)(59)(60)(61).…”
Section: Discussionmentioning
confidence: 99%
“…Appel et al [188], however, found that increasing the linoleic acid content of the diet did not increase pancreatic carcinogenesis in either rats or hamsters. Birt et al [185] found that feeding a saturated fat [beef tallow] enhanced pancreatic carcinogenesis in hamsters greater than a polyunsaturated fat [corn oil]. In transgenic models, increasing dietary corn oil led to a higher incidence and size of pancreatic ductal neoplasia in elastase-Kras mice [189] and in PDX-1-Cre;LSL-KRAS G12D mice [190].…”
Section: Pancreatic Cancermentioning
confidence: 99%
“…It has been shown that a high-corn oil diet increased pancreatic ductal adenocarcinoma development in BOP-treated hamsters as compared with a low-corn oil diet [69]. Furthermore, a diet containing beef tallow has been shown to increase pancreatic cancer development compared with a diet containing corn oil [70]. Type and composition of fat are considered to be important.…”
Section: Modifying Factors In the Experimental Pancreatic Carcinogenementioning
confidence: 99%